Risk of Tuberculosis Among Patients on Dialysis: The Predictive Value of Serial Interferon-Gamma Release Assay. Issue 22 (May 2016) - Shu, Chin-Chung; Hsu, Chia-Lin; Wei, Yu-Feng; Lee, Chih-Yuan; Liou, Hung-Hsiang; Wu, Vin-Cent; Yang, Feng-Jung; Lin, Hsien-Ho; Wang, Jann-Yuan; Chen, Jin-Shing; Yu, Chong-Jen; Lee, Li-Na
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Patients on long-term dialysis are at high risk for tuberculosis (TB). Although latent tuberculosis infection (LTBI) is good target for TB eradication, interferon-gamma release assay-defined LTBI has a high proportion of negative conversion and lacks active TB correlation among patients on dialysis. Patients on long-term dialysis were screened in multiple centers in Taiwan. QuantiFERON-TB Gold In-tube (QFT-GIT) was used to define LTBI and was performed thrice at 6-month intervals. The primary outcome was active TB diagnosed after LTBI screening. The incidence and predictive value of QFT-GIT were analyzed. The 940 dialysis patients enrolled had an average age of 59.3 years. The initial QFT-GIT results were positive in 193, including 49.6% with persistent positive results on second check. In an average follow-up period of 3 years, 7 patients had TB. Three (319.1 per 100, 000 person-yrs) and 4 (141.8 per 100, 000 person-yrs) of them were prevalent and incident TB cases, respectively. Persistent positive QFT-GIT for 2 and 3 times correlated with increased hazard ratio for TB (14.44 and 20.29, respectively) compared with a single positive result (hazard ratio 10.38). Among those with 3 positive QFT-GIT results, TB development rate was 4.5% and incidence rate was 1352.3 per 100, 000 person-years. In contrast, none of the incident TB occurred in those with initial positive and then negative conversion of QFT-GIT. In an area of intermediate TB incidence, dialysis patients have high TB risk. LTBI status is a good predictor of TB development, especially for those with more than 1 positive result. After excluding prevalent TB cases, serial follow-up of LTBI may narrow the target population to reduce treatment costs.